Tăng cường các biện pháp an ninh đối với tàu bay của Vietnam Airlines - Nguyễn, Thanh Quý (2011)
Tác giả: Nguyễn Thanh Quý, CN; Nguyễn Quốc Động, KS; Nguyễn Văn Linh, CN; Hoàng Duy Khánh, CN; Đỗ Thị Dung, CN -- Từ khóa: An ninh; An ninh hàng không; Vietnam Airlines; Hàng không Việt Nam